Analisis Kemampuan Literasi Matematika Siswa Setelah Mengalami Pembelajaran dengan Pendekatan Metakognitif-Diskursif - Timotius Woda Napu (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to determine the mathematical literacy abilities of class VIII students of SMPK St. Paulus Karuni in the subject of One Variable Linear Equations after experiencing a learning process using a metacognitive-discursive approach. The type of research used in this research is descriptive qualitative research. Data collection methods used are tests and interviews. The data analysis technique used is data reduction, data presentation and conclusion. The mathematical literacy ability of class VIII students of SMPK St. Paulus Karuni in the material Linear Equation One Variable based on Bloom's taxonomy level for each question is as follows: (1) for problem 1, there are eight out of nine students who reach level 5 or fulfill the first five indicators of Bloom's taxonomy, and one out of nine students can achieve level 4 or fulfilling the first four indicators of Bloom's taxonomy; and (2) for question 2, there were seven out of nine students who reached level 5 or fulfilled the first five indicators of Bloom's taxonomy, and two of the nine students reached level 3 or were able to fulfill the first three indicators of Bloom's taxonomy